Karyotypical Identification of Some Important Alfalfa (Medicago sativa L.) Lines in Turkey - Uğur Özkan; Berk Benlioğlu (Turkish Journal of Agriculture: Food Science and Technology)
Chromosome line and characterization of nine Turkish alfalfa (Medicago sativa L.) lines were investigated using karyological techniques in this study. Root tips were obtained from germinated alfalfa seeds in petri dishes at room temperature (25°C) for visualizing somatic chromosomes. The chromosome numbers of nine alfalfa lines were determined as 2n=4x=32. The karyotype formula of 2n=32= 30m+ 2sm (30 median + 2 submedian) were noted for Line 1, 2and 3. Whereas, Line 4, 6, 8, 9 showed the karyotype formula of 2n=32=32m (32 median). The karyotype formula of Line 5 and 7 were 2n=32=28m+4sm (28 median + 4 submedian). Satellite chromosome pairs were observed from Line 5. The results of the karyotype asymmetry index analysis showed that intrachromosomal asymmetry is higher than interchromosomal asymmetry in the karyotypes of alfalfa lines.